Ill Effects of Smoking: Baseline Knowledge among School Children and Implementation of the “AntE Tobacco” Project - Salim Surani; Raghu Reddy; Amy E. Houlihan; Brenda Parrish; Gina L. Evans-Hudnall; Kalpalatha Guntupalli (International Journal of Pediatrics)
Introduction. Cigarette smoking contributes to the deaths of more than 400,000 Americans annually. Each day >3,000 children and adolescents become regular smokers. This paper details a new antitobacco educational program titled “AntE Tobacco” Method. Children in grades 1–3 were administered a 10-item questionnaire to ascertain their baseline knowledge about the ill effects of smoking, shown an educational cartoon video depicting the ill effects of tobacco, and given a story book based on the video. At the end of video, children were administered a questionnaire to determine short-term recall of the antitobacco educational objectives of the program. Four to 6 weeks later, the children were then administered a follow-up survey to determine long-term retention of the anti tobacco educational program. Result. Eighty two percent of the children answered the outcome questions correctly immediately following the video. At follow-up, 4–6 weeks later, 83% of children answered all questions correctly. Conclusion. The anti tobacco education program used in this study effectively conveyed most of the educational objectives. The results of this study indicate that a multimedia (i.e., video and book) educational program can be used to educate and reinforce anti tobacco messages. This program may be very useful as a part of a comprehensive anti tobacco curriculum in school systems.